Evaluation of the performance and achievements of the WHO Evidence-informed Policy Network (EVIPNet) Europe - Louise Lester; Michelle M. Haby; Evelina Chapman; Tanja Kuchenmüller (BMC, 2020)
Abstract Background The Evidence-informed Policy Network (EVIPNet) is one of the key mechanisms introduced by WHO to reduce the research-to-policy gap. EVIPNet Europe was launched in 2012. We evaluated the performance and achievements of EVIPNet Europe with the overall aims (1) to inform future developments and strategic planning of EVIPNet Europe and (2) to contribute to the evidence base for organisational knowledge translation activities by sharing the lessons learnt. Methods The evaluation covered the WHO Secretariat of EVIPNet Europe and its 21 member countries, from its inception to mid-2018. A mixed methods design was used to assess changes in three domains, including triangulation of quantitative and qualitative methods, based on the EVIPNet Europe Monitoring & Evaluation framework and theory of change. Data were collected between August and October 2018. Data collection comprised documentary review, social media analysis, online country evaluation, key informant interviews and validated tools. Two case studies were also developed. Results The evaluation showed promising results as well as lessons to guide the future development of EVIPNet in the WHO European Region and other regions of the world. EVIPNet Europe appears to be filling a niche in promoting the capacity of Network member countries for evidence-informed policy-making. There is evidence that EVIPNet Europe's capacity-building programme of work is improving knowledge and skills at the individual level. There has been an increase in activity and outputs since its establishment and evidence has been used to inform new policies in some member countries. However, the speed at which member countries are developing or publishing products varies greatly and no formalised knowledge translation platforms have yet been created. Financial and human resources are limited and staff turnover is a cause for concern, both at the WHO Secretariat and country team levels. Conclusions Six years since the launch of EVIPNet Europe, the Network has grown quickly, is clearly valued and has had some successes. However, more work and support are needed if it is to achieve its vision of a Europe in which high-quality, context-sensitive evidence routinely informs health decision-making processes that ultimately serve to strengthen health outcomes across the Region.